Impact of Digital Transformation on Administrative Management: Perspectives from Cloud Computing and Big Data in Industry 4.0 - Paucar, Luis Miguel Mejía; Larico, Juan Carlos Pinto; Hancco, Cesar Apaza; Apaza, Jackeline Flores (Journal of Ecohumanism, 2025)
Digital transformation is revolutionizing administrative management by integrating technologies such as cloud computing and Big Data within the framework of Industry 4.0. This article explores how these tools drive efficiency, data-driven decision-making, and business competitiveness. Recent implementation cases, the advantages of digitalization and the associated challenges, such as data security and resistance to organizational change, are analyzed. The research uses a qualitative and quantitative approach, based on academic studies and interviews with experts in the sector. The results show a significant improvement in operational agility and a reduction in costs, although barriers to technology adoption persist.